2019
DOI: 10.1186/s13049-019-0676-5
|View full text |Cite
|
Sign up to set email alerts
|

The Danish prehospital emergency healthcare system and research possibilities

Abstract: The emergency medical healthcare system outside hospital varies greatly across the globe - even within the western world. Within the last ten years, the demand for emergency medical service systems has increased, and the Danish emergency medical service system has undergone major changes.Therefore, we aimed to provide an updated description of the current Danish prehospital medical healthcare system.Since 2007, Denmark has been divided into five regions each responsible for health services, including the preho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
122
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 113 publications
(141 citation statements)
references
References 18 publications
0
122
0
Order By: Relevance
“…Calls to the national emergency number 1-1-2 concerning acute health problems are redirected to EMCC, where the nurses/paramedics use a criteriabased dispatch protocol to assess the level of urgency and the most adequate response. 1,2 We considered OOH as 4 P.M to 8 A.M on workdays and all hours on weekends and public holidays (GPC hours). Danish health care is tax-financed and free of charge, including the EMS and OOH-PC services.…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Calls to the national emergency number 1-1-2 concerning acute health problems are redirected to EMCC, where the nurses/paramedics use a criteriabased dispatch protocol to assess the level of urgency and the most adequate response. 1,2 We considered OOH as 4 P.M to 8 A.M on workdays and all hours on weekends and public holidays (GPC hours). Danish health care is tax-financed and free of charge, including the EMS and OOH-PC services.…”
Section: Settingmentioning
confidence: 99%
“…Even though the EMS and many OOH-PC services use telephone triage to assess the most adequate response to the patient's condition, the patient or bystander makes the initial choice of contacting a service and which service to contact. [1][2][3] So far, studies on patient characteristics associated with contacting an acute health care setting have either included patients contacting EMS or OOH-PC and mostly focus has been on inappropriate or recurrent use. [4][5][6][7][8] However, possible overlaps in the EMS and OOH-PC patient populations have been observed; some patients in need of acute care contact OOH-PC and some patients with non-specific complaints perhaps more suitable for OOH-PC contact EMS.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately half of the confirmed cases were in the Capital Region of Denmark (9). The Danish EMS system is organized into five regions with similar structures serving ambulances, physician staff vehicles and emergency medical dispatch centers (EMDC) (10). The Capital Region of Denmark, Copenhagen, has 1.8 million inhabitants served by the Copenhagen EMS.…”
Section: Introductionmentioning
confidence: 99%
“…Some crowding can be reduced by better integration of community, ambulance and hospital information systems. Experience from Denmark and the Netherlands has shown that primary care and advice lines can have an effective role in providing alternative services and that this can reduce ED attendances 7 8. Lower acuity patients should be offered responsive alternatives to ED care.…”
mentioning
confidence: 99%